Optimizing centrifugal water pump design for enhanced water use efficiency in Batam Marina Plantations - Asmarawati, Citra Indah; Wibowo, Sadiq Ardo; Gumilang, Reno Reza (Universitas Sultan Ageng Tirtayasa, 2025)
Water demand in the plantation area has been increasing by 6% per year due to population growth, making the existing main water pump insufficient. To address this, a new centrifugal pump was designed with a focus on efficiency and ease of assembly using the Design for Manufacture and Assembly (DFMA) method and the French design analysis method. This study aims to develop an optimal pump design with an estimated service life of over five years, ensuring a reliable and sustainable water supply for the plantation area. The DFMA analysis showed that the design efficiency index improved from 0.30% in the current design to 0.77% in the alternative design—an increase of 0.47%. The alternative design was chosen because it offers faster assembly, lower costs, and fewer components compared to the existing model. Beyond improving efficiency, the optimized centrifugal pump is expected to last more than five years. This durability is supported by using corrosion-resistant grade 316 stainless steel for key components, material strength tests through finite element analysis (FEA) simulations under maximum operating conditions, and fatigue testing on the impeller, which confirmed its ability to withstand repeated use.